Associative Plasticity in the Medial Auditory Thalamus and Cerebellar Interpositus Nucleus during Eyeblink Conditioning - Halverson, Hunter E. (Society for Neuroscience, 2010)
Eyeblink conditioning, a type of associative motor learning, requires the cerebellum. The medial auditory thalamus is a necessary source of stimulus input to the cerebellum during auditory eyeblink conditioning. Nothing is currently known about interactions between the thalamus and cerebellum during associative learning. In the current study, neuronal activity was recorded in the cerebellar interpositus nucleus and medial auditory thalamus simultaneously from multiple tetrodes during auditory eyeblink conditioning to examine the relative timing of learning-related plasticity within these interconnected areas. Learning-related changes in neuronal activity correlated with the eyeblink conditioned response were evident in the cerebellum before the medial auditory thalamus over the course of training and within conditioning trials, suggesting that thalamic plasticity may be driven by cerebellar feedback. Short-latency plasticity developed in the thalamus during the first conditioning session and may reflect attention to the conditioned stimulus. Extinction training resulted in a decrease in learning-related activity in both structures and an increase in inhibition within the cerebellum. A feedback projection from the cerebellar nuclei to the medial auditory thalamus was identified, which may play a role in learning by facilitating stimulus input to the cerebellum via the thalamo-pontine projection.